Using Clickers to Address Common Errors and Misconceptions in Statistics. Issue 5 (28th May 2023) - Cline, Kelly S.; Huckaby, David A.; Zullo, Holly
ABSTRACT: Using clickers in the statistics classroom can help students identify and understand common errors and misconceptions through a combination of surprise and discussion. Students are presented with multiple-choice questions that they discuss with each other and then vote on; a class-wide discussion follows. Questions for which many students vote for the same wrong answer and questions that reveal a common misconception jolt students' attention and lead to fruitful discussions. To identify the questions that most effectively target misconceptions, we recorded the percentage of the class voting on each of the possible responses on every clicker question used in 28 sections of introductory statistics courses taught by 3 instructors at 2 institutions. For each question, we identified the distractor that attracted the highest percent of votes on average. We present and discuss the six questions for which this average was at least 50%. We find that each of these question statements is fairly brief and tightly focused on a particular common error or misconception.